ANALISIS TEKSTUAL BRAND TELUK LOVE MENJADI DESTINASI WISATA POPULER DI KABUPATEN JEMBER - Susanti, Ari (Universitas Muhammadiyah Jember, 2018)
Love Bay, which is located in Payangan Hamlet, Sumberrejo Village, Ambulu District, Jember Regency, is one of the most popular tourist destinations today. The word